Pengaruh People, Persepsi Harga Dan Physical Evidence Terhadap Keputusan Pembelian Mixue Prigen - Nur Ainun Jariyah; Herlinda Maya Kumala Sari; Rita Ambarwati Sukmono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research is a type of quantitative research. Collecting primary research data was carried out through a questionnaire which was filled out online using Google From and distributed with a questionnaire link via various social media. The sampling technique uses a non-probability method. The sampling technique used is non-probability, using the accidental sampling method. To measure the number of samples, considering that the population in the study is not known with certainty, the Cochran Formula is used. In calculations using the Cochran formula, the result was 96.04, so the minimum sample size was 96 samples from consumers who had purchased Mixue Prigen. The analytical tools used in this research are multiple linear regression analysis, classical assumption test, t test, R test, R2 test using the SPSS version 22 application program. The results of this research prove that People have a significant influence on purchasing decisions. Price perception has a significant influence on purchasing decisions. Physical Evidence has a significant influence on purchasing decisions. Promotions have a significant effect on purchasing decisions. Keywords: People, Price Perception, Physical Evidence on Purchasing Decisions